Comparing patient and healthcare worker experiences during a dengue outbreak in Singapore: Understanding the patient journey and the introduction of a point-of-care test (POCT) toward better care delivery - Tan Q. (BioMed Central Ltd., 2020)
10.1186/s12879-017-2580-9